2009
DOI: 10.1188/09.cjon.501-505
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients in Financial Need

Abstract: Some eligible patients with financial hardship may not be referred to assistance programs because cancer care providers do not know the full extent of patients' needs. This article describes barriers cancer care providers face in identifying patients who have financial concerns by using qualitative data from 21 interviews with providers from one Canadian province. Interviews were audio recorded, transcribed verbatim, and analyzed with a thematic approach. Four major themes emerged: no standardized approach exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…The reason for the increase in calls during Period 2 for "helpline services information" in those ≥65 may be related to the focus on outreach to older adults with cancer as part of the larger study. The findings about the ongoing need for financial assistance, help with coping issues, and a need for additional information reflect those in other research reports published after the IOM report in 2007 and suggest that the IOM recommendations have not been fully implemented into cancer care [28]- [35]. When call categories were separated by the age of the person with cancer (i.e., patient) (<65 vs. ≥65) the percent of those seeking information about financial assistance was lower in the ≥65 group (Table 3).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The reason for the increase in calls during Period 2 for "helpline services information" in those ≥65 may be related to the focus on outreach to older adults with cancer as part of the larger study. The findings about the ongoing need for financial assistance, help with coping issues, and a need for additional information reflect those in other research reports published after the IOM report in 2007 and suggest that the IOM recommendations have not been fully implemented into cancer care [28]- [35]. When call categories were separated by the age of the person with cancer (i.e., patient) (<65 vs. ≥65) the percent of those seeking information about financial assistance was lower in the ≥65 group (Table 3).…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, it was often not possible to match callers seeking financial assistance with stage of disease and age for this study. Mathews and Park suggested that people with cancer in financial need were not adequately screened by healthcare providers [35]. They cited a lack of a standardized approach to assessing the financial needs of people with cancer and reluctance of them to disclose financial concerns as barriers in indentifying patients with financial need.…”
Section: Discussionmentioning
confidence: 99%
“…Key challenges to identifying survivors in financial distress include a lack of standardized methods to assess need and the necessity of accounting for changing needs over time. 37 A recently proposed model of cancer rehabilitation that recognizes the need for comprehensive care, including attention to social and vocational needs, suggests that expanding survivorship care to include services that both promote self-management and encourage survivors to remain or return to the workforce has the potential to reduce overall cancer costs as well as costs to individual survivors 38 and should be considered as a way to reduce financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare financing and delivery changes, particularly cost-cutting efforts on the part of insurers, may widen existing gaps in access to services for racial and ethnic minorities, greatly affecting those in rural areas with diminished access to health care (DiIorio et al, 2011; Mathews & Park, 2009). Patients have identified cancer costs as contributing to treatment barriers, increasing stress, and decreasing quality of life (Klimmek, Snow, & Wenzel, 2010; Wagner & Lacey, 2004).…”
mentioning
confidence: 99%
“…Patients have identified cancer costs as contributing to treatment barriers, increasing stress, and decreasing quality of life (Klimmek, Snow, & Wenzel, 2010; Wagner & Lacey, 2004). The high cost of cancer treatment is borne by patients and caregivers (Chang et al, 2004; Mathews & Park, 2009) and may be a greater barrier to treatment for African Americans (Chu, Miller, & Springfield, 2007; Mosavel & Sanders, 2011) with significant societal consequences (Adler & Page, 2008). …”
mentioning
confidence: 99%